2014
DOI: 10.1002/aic.14354
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of higher alcohol synthesis directly from syngas over CoCu/SiO2 catalysts

Abstract: Higher alcohol synthesis (HAS) directly from syngas is one of the most promising approaches for utilizing nonoil resources cleanly and efficiently. A series of bimetallic CoCu catalysts with different Co/Cu ratios were prepared using a SiO2 support. The structure of Cu modified Co catalysts was characterized using HRTEM, in/ex situ X‐ray diffraction, and temperature‐programmed reduction. It was evidenced that nanoscale metal particles were formed and the reduction of Co oxide at above 673 K. Meanwhile, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 73 publications
3
57
0
Order By: Relevance
“…Anderson-Schulz-Flory (ASF) distribution (Eq. 14) as it is widely used in Fischer-Tropsch synthesis (Su et al, 2014;Subramanian et al, 2010).…”
Section: Asf Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson-Schulz-Flory (ASF) distribution (Eq. 14) as it is widely used in Fischer-Tropsch synthesis (Su et al, 2014;Subramanian et al, 2010).…”
Section: Asf Analysismentioning
confidence: 99%
“…The conversion of CO was kept below 10.0% in order to ensure differential condition. The external/internal diffusion effects can be ruled out following the procedures introduced by previous studies (Madon and Boudart, 1982;Su et al, 2014).…”
Section: Activity Test and Kinetic Measurementmentioning
confidence: 99%
“…1 (III). Su et al34 attributed the diffraction peaks between pure metal Co and Cu to the bimetallic Co-Cu alloy. Volkova et al18 demonstrated that the slight increase in lattice spacing for copper and a small decrease in lattice spacing for cobalt are the characteristics of the Co-Cu alloy.…”
mentioning
confidence: 99%
“…Moreover, addition of 17 the Mn to Fe or Co catalysts leads to significant increase in high 18 olefin formation and decrease in methane selectivity [12,13]. The 19 fusion method is one of the preparing catalysts methods for 20 Fischer-Tropsch synthesis. The fusing iron oxides together with 21 the chemical and structural promoters as catalyst for the high 22 temperature Fischer-Tropsch (HTFT) process applied in Sasol 23 Company [14,15].…”
mentioning
confidence: 99%
“…Actually the kinetics based on 35 CO consumption attends more than another method because the 36 products of FTS are very complicated. 37 In the many publications, intrinsic reaction rate equations for 38 the FT equation (hydrocarbon forming only) based on Langmuir- 39 Hinshelwood-Hougen-Watson (LHHW) adsorption theory have 40 been developed and used successfully for iron and cobalt-based 41 catalysts [19][20][21][22][23][24][25]. The mechanisms proposed bases in approach 42 were including the carbide, enolic, and direct insertion theories.…”
mentioning
confidence: 99%